Economic efficiency of leased lands in Romania lease versus association - Ionut Laurenţiu Petre; Eduard Alexandru Dumitru (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
Leasing is an effective method of using agricultural land in Romania? This paper will answer this question, it will analyze the impact assessment produced by leasing land, the benefit to the farmer concerned. Take into account the causes of the lease, such as inability plot work, the health of the owner, etc. It will consider the Lease Law, but also statistics on the soils in this stage. It will analyze the benefit derived by the landowner, but a comparison in terms between cooperation and farmers association. The comparative study will be made in two distinct cases: first, the owner gives the agricultural goods and the second the same beneficiary can be integrated or may give rise to an association of owners. In the end will determine whether leasing land is indeed an effective method of "exploitation" of the land, or if is a more "comfortable". It will make some recommendations, some relating to negotiating and arranging the lease, others about association, but also recommendations about legislation.
Keywords: Q12; Q15; 330; leasing land; producer associations; economic efficiency; legislation